2021
DOI: 10.1371/journal.pone.0249527
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary chromium picolinate supplementation on broiler growth performance: A meta-analysis

Abstract: Objective A meta-analysis was conducted to assess the effects of dietary chromium picolinate (CrPic) supplementation on broiler growth performance and to determine whether such effects are regulated by broiler strains, sex, environmental stress, or contextual factors including study area and years. Methods Eligible studies were identified by searching the Web of Science, Springer, Elsevier, ScienceDirect, Taylor & Francis Online databases. Weighted average differences with corresponding 95% confidence in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
6
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 40 publications
3
6
0
2
Order By: Relevance
“…The combined use of a probiotic and a chelated form of Cr positively affected broiler chickens’ meat productivity, which was characterized by increases in the average daily gain of birds and body weight, resulting in an increased slaughtered carcass yield. The obtained results are consistent with a number of global studies in which the inclusion of various forms of Cr in feed contributed to an increase in body weight gain in animals and improvements in carcass characteristics and meat quality [ 22 25 ]. In particular, Arif et al .…”
Section: Discussionsupporting
confidence: 90%
“…The combined use of a probiotic and a chelated form of Cr positively affected broiler chickens’ meat productivity, which was characterized by increases in the average daily gain of birds and body weight, resulting in an increased slaughtered carcass yield. The obtained results are consistent with a number of global studies in which the inclusion of various forms of Cr in feed contributed to an increase in body weight gain in animals and improvements in carcass characteristics and meat quality [ 22 25 ]. In particular, Arif et al .…”
Section: Discussionsupporting
confidence: 90%
“…Thus, it is difficult to identify the clear reason; however, it may be attributed to the variations in animals and environmental conditions among the experiments because the extent of heat stress is influenced by both animal (e.g., sex, age, and genetics) and environmental factors (e.g., stocking density, ambient temperature and humidity, duration and the extent of heat stress, and rearing facility) [ 5 , 13 ]. However, we found that all functional nutrients used in this experiment showed the reduction in stress responses measured based on feather CORT concentrations and blood H:L. Therefore, it may be suggested that dietary supplementation of 0.5% Gln, 500 ppb Cr picolinate, 250 mg/kg Vit C, 0.2% Bet, and 1.0% Tau is effective in reducing stress responses of broiler chickens under heat stress conditions; however, these anti-heat stress effects are unlikely to lead to a full recovery of decreased growth performance of broiler chickens raised under the current heat stress conditions [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…Heat stress is well-known to depress immune systems because increased corticosteroid production and impaired immune organ development as caused by heat stress exerts a strong negative impact on immune systems [ 3 , 13 , 45 ]. Moreover, heat stress promotes oxidative stress, which increases lipid peroxidation of cell membrane of potential immune-related cells, leading to an impairment in immune responses [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The same effect was reported by Naghieh et al ( 2010 ) with 600 µg/kg Cr nicotinate, by Noori et al ( 2012 ) with Cr methionine from 200 to 800 ppb, and by Toghyani et al ( 2012 ) with 1500 ppb organic or inorganic Cr. Recently, Feng et al ( 2021 ) found that Cr picolinate supplementation had a positive effect on the growth performance of broilers. It is well recognized that chromium is essential for proper insulin functioning and also needed for normal protein, fat, and carbohydrate metabolism (Chowdhury et al, 2003 ).…”
Section: Discussionmentioning
confidence: 99%